Internationalization of K-12 Schooling through Virtual Exchange: Opportunities in a Fractured Context - Hinshaw, Nicole; Gonzalez, Stephanie; Engel, Laura (Journal of International Students, 2022)
This study considers the opportunities and barriers facing the implementation of virtual exchange in K-12 education, and the perceptions of access to these opportunities for underrepresented students, in the context of the federal US education system. These questions are examined through the lens of a domestic program offered by Empatico known as Empathy Across the US. Our findings point to several of the known barriers in the facilitation of virtual exchange, including technology access and pressing demands facing teachers, both of which impact accessibility. This study offers insights into how teachers in different settings perceive and experience the implementation of a domestic model of virtual exchange. As K-12 virtual exchange programs often rely on the willingness of teachers to implement these kinds of programs outside of the official school curriculum, our research indicated the importance of system-wide investment and structural support for domestic virtual exchange beyond individual champions.